2020
DOI: 10.1007/s00405-020-06293-0
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve for endoscopic tympanoplasty type I: comparison of endoscopic-native and microscopically-trained surgeons

Abstract: Purpose Type I tympanoplasty is one of the first operations to be performed by ear surgeons in training and is increasingly performed using the endoscopic technique. The aim of the present study is to assess and compare the learning curve for type I tympanoplasties between a microscopically trained and endoscopic native ear surgeon. We hypothesize comparable learning curves between the two surgeons regardless of previous microscopic experience. Methods Retrospective analysis and comparison of the 25 first cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Especially in the setting of anterior perforations, the endoscope offers enhanced view on the perforation edges and may therefore facilitate correct positioning of the graft, although the latter might be more challenging in one-handed surgery 5 . This might be confirmed by the fact that the anatomical and functional results of endoscopic type I tympanoplasties by "native" endoscopic ear surgeons are comparable to those already trained in the microscopic technique 7 .…”
Section: Introductionmentioning
confidence: 78%
“…Especially in the setting of anterior perforations, the endoscope offers enhanced view on the perforation edges and may therefore facilitate correct positioning of the graft, although the latter might be more challenging in one-handed surgery 5 . This might be confirmed by the fact that the anatomical and functional results of endoscopic type I tympanoplasties by "native" endoscopic ear surgeons are comparable to those already trained in the microscopic technique 7 .…”
Section: Introductionmentioning
confidence: 78%
“…The graft failure rate of type I ET is approximately 10%–15% 9–11 . Most study results have shown similar success rates for conventional microsurgery and endoscopic surgery 12 .…”
Section: Discussionmentioning
confidence: 98%
“…Several potential challenges and disadvantages of TEES are worth noting. A longer learning curve has been suggested, though this may be less relevant to current and future generations of surgeons who receive early training in endoscopic techniques 37 . One recent series even demonstrated a shorter operative time than a microscopic technique for the management of cholesteatoma 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A longer learning curve has been suggested, though this may be less relevant to current and future generations of surgeons who receive early training in endoscopic techniques. 37 One recent series even demonstrated a shorter operative time than a microscopic technique for the management of cholesteatoma. 17 There is a loss of binocular vision that is afforded by the microscope; however, this is overcome by the dynamic visualization provided by the endoscope.…”
Section: Discussionmentioning
confidence: 99%